לפשט את הביטוי ?: 1 / (sqrt (144) + sqrt (145)) + 1 / (sqrt) (145) + sqrt (146)) + + 1 / (sqrt (168) + sqrt (169))

לפשט את הביטוי ?: 1 / (sqrt (144) + sqrt (145)) + 1 / (sqrt) (145) + sqrt (146)) + + 1 / (sqrt (168) + sqrt (169))
Anonim

תשובה:

#1#

הסבר:

ראשית, שים לב:

מס '(1) / (n + 1) + sqr (n)) = (sqt (n + 1) -qqrt (n)) 1) -qqrt (n)) #

# (1) (1) (n + 1) + sqr (n)) = (sqrt (n + 1) -qqrt (n)) / (n + 1)

# (1) (n + 1) -qqrt (n) #

לכן:

# 1 / sqrt (144) + sqrt (145)) + 1 / (sqrt) (145) + sqrt (146)) + + 1 / (sqrt (168) + sqrt (169)) #

(#) (+) (+) (+) (+) (+) +

# = sqrt (169) -sqrt (144) #

#=13-12#

#=1#